SCALE EFFICIENCY IN THE TURKISH BANKING SECTOR: EVALUATION WITH WINDOW ANALYSIS (Third Sector Social Economic Review, 2021)
A strong economy can be achieved with a well-functioning and developing financial system. In the Turkish economy, the banking sector operates as the structure with the highest share fulfilling its intermediary role in the financial system. The aim of the study is to examine the scale efficiency and productivity level of the banking sector, which has such an important role and share in the economic system. For this purpose, 15 private and foreign capital deposit banks operating in the Turkish banking sector are selected as the decision-making unit. The scale efficiency of the banks are calculated with the Data Envelopment Analysis Window method using the data of two different periods, 2000-2012 and 2013-2020, of the selected banks. As a result, when the scale efficiency scores of the Turkish banking sector are evaluated in the first period, it can be concluded that it exhibited a durable stance against the 2008 Global Financial Crisis. In the second analysis period, it is observed that the efficiency values increased even more and the total number of efficient banks increased significantly in some years.
Keywords: Turkish Banking Sector; Scale Efficiency; Data Envelopment Analysis; A Window Analysis